Aeneidos - Virgil, 71 BCE-20 BCE (Salt Lake City, UT : Project Gutenberg, 1995)
"Aeneidos" by Virgil is a Latin epic poem written between 29 and 19 BC. It tells the legendary story of Aeneas, a Trojan hero who flees the fall of Troy and journeys to Italy, where he becomes the ancestor of the Romans. The first half chronicles his perilous wanderings across the Mediterranean, while the second half depicts the Trojans' war against the Latins. This founding myth connects Rome to the legends of Troy and glorifies traditional Roman virtues. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Aeneid
Release date is 1995-03-01
Keywords: Aeneas (Legendary character) -- Poetry; Legends -- Rome -- Poetry; Epic poetry, Latin